Crusading Against Christians in the Middle Ages
XIV, 384 p.
Keywords: This is the first book-length study into crusading against Christians, examining this complex phenomenon from the twelfth to fifteenth centuries and across numerous regions, from France to Russia and from southern Italy to the Baltic. Whilst the crusades are an immensely popular topic, those launched against Christian rulers and communities have been comparatively overlooked in the past, with existing studies typically focusing on a particular area, period, or campaign. This volume brings together the expertise of thirteen scholars on a variety of primary and secondary sources not often accessible to Anglophone readership, as well as their knowledge of national discourses which have often shaped historiography. It aims to serve as the first port of call for anyone who wishes to approach crusades against Christians within and without the specialism of crusader studies, and to provide the basis for a thorough comparative analysis of this phenomenon, covering its variety as comprehensively as possible. Mike Carr is Senior Lecturer in Late Medieval History at the University of Edinburgh, Edinburgh, UK. His work focuses on the interactions between Latins, Byzantines and Muslims in the Mediterranean, especially the role of merchants and religious institutions in cross-cultural trade and religious conflict. He is the author of Merchant Crusaders in the Aegean, 1291-1352 (2015), and co-editor of Contact and Conflict in Frankish Greece and the Aegean, 1204-1453 (2014), The Military Orders Volume 6.1-6.2: Culture and Contact (2016), and Military Diasporas: Building of Empire in the Middle East and Europe (550 BCE-1500 CE) (2022). Nikolaos G. Chrissis is Assistant Professor of Medieval European History at the National and Kapodistrian University of Athens, Greece. His research interests and publications revolve around the crusades, Latin presence in Greek lands, Byzantine-Western relations, papal policy in the Levant, and generally intercultural contacts in the medieval Mediterranean. He is the author of Crusading in Frankish Greece: A Study of Byzantine-Western Relations and Attitudes, 1204-1282 (2012), and co-editor of Contact and Conflict in Frankish Greece and the Aegean, 1204-1453 (2014) and Byzantium and the West: Perception and Reality, 11th-15th c. (2019). Gianluca Raccagni is Senior Lecturer in Medieval History at the University of Edinburgh, UK. His research interests focus on political culture in the central Middle Ages, especially within Communal Italy but also its relations with the rest of Europe, the Mediterranean, and the crusades. Most recently he has been exploring contacts between the Mediterranean and the Nordic World in the eleventh century. He is author of The Lombard League (1167-1225) (2010) and of several journal articles.